2017
DOI: 10.1093/icb/icx076
|View full text |Cite
|
Sign up to set email alerts
|

Systems Biology of Phenotypic Robustness and Plasticity

Abstract: Synopsis Gene regulatory networks, cellular biochemistry, tissue function, and whole body physiology are imbued with myriad overlapping and interacting homeostatic mechanisms that ensure that many phenotypes are robust to genetic and environmental variation. Animals also often have plastic responses to environmental variables, which means that many different phenotypes can correspond to a single genotype. Since natural selection acts on phenotypes, this raises the question of how selection can act on the genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 81 publications
4
50
0
Order By: Relevance
“…This has led to the proposal of a modified version of the mutation accumulation theory of ageing, in which the deleterious effects of mutations are present throughout life, but increase in magnitude with age (Maklakov et al, 2015). Interestingly, this idea is concordant with recent thinking on the evolution of cancer (DeGregori, 2011), as well as with complex systems explanations of ageing as a breakdown in homeostasis (Cohen, 2012(Cohen, , 2016: physiological regulatory networks are highly buffered and redundant, and loss of homeostasis in a given subnetwork thus is most likely to be expressed in the presence of other problems in the same or connected subnetworks (Nijhout, Sadre-Marandi, Best, & Reed, 2017). Early in life, buffering is likely to better mask the effects of mutations than later on when increasing dysregulation exposes the consequences of the mutation.…”
Section: Trade-offs In Experimental Evolution Of Model Organismssupporting
confidence: 70%
“…This has led to the proposal of a modified version of the mutation accumulation theory of ageing, in which the deleterious effects of mutations are present throughout life, but increase in magnitude with age (Maklakov et al, 2015). Interestingly, this idea is concordant with recent thinking on the evolution of cancer (DeGregori, 2011), as well as with complex systems explanations of ageing as a breakdown in homeostasis (Cohen, 2012(Cohen, , 2016: physiological regulatory networks are highly buffered and redundant, and loss of homeostasis in a given subnetwork thus is most likely to be expressed in the presence of other problems in the same or connected subnetworks (Nijhout, Sadre-Marandi, Best, & Reed, 2017). Early in life, buffering is likely to better mask the effects of mutations than later on when increasing dysregulation exposes the consequences of the mutation.…”
Section: Trade-offs In Experimental Evolution Of Model Organismssupporting
confidence: 70%
“…As before, an analysis of the virtual population may identify the particular combinations of parameter values that make individuals more or less susceptible to develop low serotonin. An example of such a study, for individual variation of dopamine levels, is shown in Figure of Nijhout et al (). Relating deterministic models to biological data. Imagine an experiment where a experimenter changes the input to a biochemical network for a short period of time and then measures the values of a particular concentration over time. If the experiment is repeated several times, somewhat different curves will be obtained, and the experimenter will report the mean curve and the standard deviations.…”
Section: Mechanisms Of Homeostasismentioning
confidence: 99%
“…It is this family of model output curves that should be compared to the family of experimental curves, not just the average model curve to the experimental mean curve, because there is real biological information in the dispersion of the curves. Thus, system population models are the right way to compare mechanistic ODE models to real biological data. Identifying important subpopulations. A systems population model can be “treated” with a drug, or given a specific nutrient or vitamin deficiency, and the resulting population can be compared with a untreated population (Nijhout et al, ). Not all individuals will respond similarly, and statistical analyses of the two populations can be used to identify genetic make‐ups (i.e., specific combinations of parameter values) that make individuals particularly sensitive, or resistant, to the treatment.…”
Section: Mechanisms Of Homeostasismentioning
confidence: 99%
“…Indeed, the genetic basis of adaptation is often inferred to be due to differences in gene expression (Chan et al, ; Gompel, Prud'homme, Wittkopp, Kassner, & Carroll, ; Hoekstra & Coyne, ; Jeong et al, ; Pai & Gilad, ; Signor, Liu, Rebeiz, & Kopp, ; Wray, ; Yassin et al, ). This balance between stability and lability is a question that has been addressed philosophically, but little experimental evidence exists to suggest the mechanisms underlying these phenomena (Casci, ; Gibson, ; Green et al, ; Heranz & Cohen, ; Hermisson & Wagner, ; Nijhout et al, ; Rutherford et al, ; Stern, ; True & Haag, ).…”
Section: Introductionmentioning
confidence: 99%
“…Pai & Gilad, 2014;Signor, Liu, Rebeiz, & Kopp, 2016;Wray, 2007;Yassin et al, 2016). This balance between stability and lability is a question that has been addressed philosophically, but little experimental evidence exists to suggest the mechanisms underlying these phenomena (Casci, 2005;Gibson, 2009;Green et al, 2017;Heranz & Cohen, 2010;Hermisson & Wagner, 2004;Nijhout et al, 2017;Rutherford et al, 2007;Stern, 2000;True & Haag, 2001).…”
Section: Introductionmentioning
confidence: 99%